Carotid anatomy does not predict the risk of new ischaemic brain lesions on diffusion-weighted imaging after carotid artery stenting in the ICSS-MRI substudy - Doig, D; Hobson, B; Müller, M; Jäger, H; Featherstone, R; Brown, M; Bonati, L; Richards, T (Elsevier, 2015)
Introduction The International Carotid Stenting Study (ICSS, ISRCTN25337470) randomized patients with recently symptomatic carotid artery stenosis>50% to carotid artery stenting (CAS) or endarterectomy. CAS increased the risk of new brain lesions visible on diffusion-weighted magnetic resonance imaging (DWI-MRI) more than endarterectomy in the ICSS-MRI Substudy. The predictors of new post-stenting DWI lesions were assessed in these patients. Methods ICSS-MRI Substudy patients allocated to CAS were studied. Baseline or pre-stenting catheter angiograms were rated to determine carotid anatomy. Baseline patient demographics and the influence of plaque length, plaque morphology, internal carotid angulation, and external or common carotid atheroma were examined in negative binomial regression models. Results A total of 115 patients (70% male, average age 70.4) were included; 50.4% had at least one new DWIMRI-positive lesion following CAS. Independent risk factors increasing the number of new lesions were a leftsided stenosis (incidence risk ratio [IRR] 1.59, 95% CI 1.04e2.44,p<.03), age (IRR 2.10 per 10-year increase in age, 95% CI 1.61e2.74,p<.01), male sex (IRR 2.83, 95% CI 1.72e4.67,p<.01), hypertension (IRR 2.04, 95% CI 1.25e3.33,p<.01) and absence of cardiac failure (IRR 6.58, 95% CI 1.23e35.07,p<.03). None of the carotid anatomical features significantly influenced the number of post-procedure lesions. Conclusion Carotid anatomy seen on pre-stenting catheter angiography did not predict of the number of ischaemic brain lesions following CAS.